Production of Acetone, Butanol and Ethanol as Bioenergy Source Materials by Clostridium saccharoperbutylacetonicum N1-4 (ATCC 13564) using Different Substrates - HANIES AMBARSARI; KENJI SONOMOTO (Indonesian Society for microbiology, 2013)
In the effort of developing bioenergy source materials, a laboratorium study was performed to investigate the effects of substrate types and concentrations on the production of acetone-butanol-ethanol (ABE) from various substrates by Clostridium saccharoperbutylacetonicum N1-4 (ATCC 13564) in defined TYA (Tryptone-Yeast extract-Acetate) media. The results demonstrated that the ABE ratios produced by the strain N1-4 were greatly influenced by the types of substrate and the concentrations being used. It was also shown that fermentation of disaccharides (cellobiose and dextrin) by the strain N1-4 could give relatively as high butanol and ABE yields as glucose fermentation after 24 h fermentation time. The strain N1-4 was also found to be able to ferment xylans from birchwood sources producing a relatively high ABE concentration, especially at a prolonged incubation time (after 48 h incubation period). A subsequent experiment using several different concentrations of glucose or cellobiose revealed that the higher the concentration of the substrate being used, then the higher the total ABE concentration or productivity could be obtained but not necessarily in the same increasing ratio. To the best of our knowledge, there was no other previous study about the effect of substrate type and concentration on the ABE ratio by C. saccharoperbutylacetonicum N1-4 (ATCC 13564) using various substrates in defined TYA media, specifically by using xylans and dextrin substrates.